Ves Function (Variable Elasticity of Substitution) in the Evaluation of Factors Substitution Shaping a Website's Usability - Chmielarz, Witold (Advanced Information Technologies for Management – AITM 2008, 2008)
The main aim of this article is presenting a new form of a production function of VES class as a potential tool for evaluating the substitutability of factors influencing the websites' performance. After remarks placing this paper in the series of studies into websites, a proposed form of VES function is characterized. Then the author presents the outline of a proof that this function fulfils the assumptions of the production function. The article is concluded with an attempt to present an economic interpretation of the function coefficients and conclusions concerning further research in this direction.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 35, s. 47-57